Закономерности изменений гидрологического, гидрохимического и гидробиологического режима р. Днепр при зарегулировании стока и их влияние на биологию рыб и санитарное состояние водохранилищ - Цееб, Я.Я.; Алмазов, А.Μ.; Владимиров, В.И. (Гидробиологический журнал, 1966)
В данной статье мы ставим перед собой задачу наиболее кратко осветить основные закономерности изменения режима реки в условиях зарегулированного стока, а также влияние этих изменений на биологию рыб и санитарное состояние водохранилищ. Надеемся привлечь внимание широкой научной общественности к обсуждению выдвинутых в статье положений, что приведет к более четкому и полному выявлению последствий гидростроительства на больших реках и будет полезным в практическом и теоретическом отношении. The results are presented of investigations, conducted for many years (1955—1965), on the Dnieper River and its reservoirs. Changes have been found in the nature of the flow-off as a result of the construction of water-power plant dams, in particular, under the effect of flow-off curtailment in the lower reaches of the Dnieper and Dnieper — Bug estuaries. It is shown that changes have occurred in the biological productivity (fish productivity) of these basins — the fish catch being reduced to about one — half. In the reservoirs created on the Dnieper the fish catch will increase by 6—7 times after their completion. The regularities in the changes of hydrochemical flow-off, plankton flow-off, peculiarities of formation of the hydrochemical and biological regime of the reservoirs (bac-terio-, phyto-, zooplanktonic, bacterio-, phyto-, zoobenthic) are discussed in the paper. The results are presented of investigations on fish reproduction in the Kremenehug and Kakhovka reservoirs. The causes and conditions for summer and winter asphyxia of fish and for changes in the sanitary state of the reservoirs are also considered.